Global Change: Impacts on Traditional Rainwater Harvesting Systems in Campo de Cartagena (Region of Murcia, Spain) - Castejón Porcel, Gregorio; Espín-Sánchez, David; García-Marín, Ramón (Land, 2026)
The effects of global change on the planet are undeniable, especially in terms of climate change, which is alarming in regions with water resource deficiencies, such as arid and semi-arid territories. One such territory is the Region of Murcia (Spain), in the southeast of which lies the Campo de Cartagena region. It is place where rainwater has historically been essential for settlement and traditional agricultural and livestock farming, giving rise to a valuable, now-forgotten water heritage. Through historical, spatial, climatic, and statistical analysis, we aim to demonstrate the significant implementation of these infrastructures in the study area and identify the causes of their abandonment, despite the continued increase in demand for water by all economic sectors, especially the agricultural, urban and tourism sectors. The results demonstrate the existence of five traditional runoff management infrastructures (cisterns, dams, runoff water channels, terracing and benching), and that the effects of global change have been decisive in their neglect, especially those related to climate change and land use modifications, in addition to increased demographic and socioeconomic pressure.
Keywords: global change; rainwater; traditional water management; agriculture; hydraulic heritage; GIS; CORINE land cover